Loneliness and Mental State in Cancer - Medine Koç; Havva Tel; Mustafa Başak; Hatice Tel Aydın; Çağdaş Akkaya; Özge Kısaoğlu (Global Nursing Insights, 2026)
Aim: In many ways, the diagnosis of cancer affects the individual's mental health as well as their physical health. Cancer patients may experience a complex emotional state, loneliness, and isolation at different levels during the disease process. This study was conducted to determine the mental status and loneliness of patients diagnosed with cancer.Material and Methods: This descriptive study was conducted with 185 patients diagnosed with cancer. The research data were collected with the Brief Symptom Inventory and the University of California, Los Angeles (UCLA) Loneliness Scale. The data were analyzed using IBM SPSS Statistics 22.0. The Mann-Whitney U test, Kruskal-Wallis test, and Spearman correlation were used to analyze the data.Results: The study found a significant difference in patients' Brief Symptom Inventory (BSI) scores based on various factors such as age, marital status, education, employment, income, illness duration, treatment, hospitalization, presence of another disease, adaptation to the disease, and perception of the disease. The UCLA Loneliness Scale scores were positively correlated with BSI total scores, as well as with the somatization and depression subscale scores (p < 0.05).Conclusions: The study concluded that a significant relationship existed between loneliness and mental problems in cancer patients, and that loneliness had a negative impact on their mental status. Based on the obtained results, we recommend a holistic approach to the treatment and care of cancer patients, to maintain their mental health and reduce their loneliness.Implication for nursing practice: This study highlights the need for nurses to assess and address loneliness and psychological distress in cancer patients. Integrating psychosocial support and therapeutic communication into nursing care may help improve patients’ mental well-being and adaptation to illness.